Discovery of serum biomarkers for diagnosis of tuberculosis by NMR metabolomics including cross-validation with a second cohort - R. Conde; R. Laires; L.G. Gonçalves; A. Rizvi; C. Barroso; M. Villar; R. Macedo; M.J. Simões; S. Gaddam; P. Lamosa; L. Puchades-Carrasco; A. Pineda-Lucena; et al. (Biomedical Journal, 2022)
Background: Tuberculosis (TB) is a disease with worldwide presence and a major cause of death in several developing countries. Current diagnostic methodologies often lack specificity and sensitivity, whereas a long time is needed to obtain a conclusive result. Methods: In an effort to develop better diagnostic methods, this study aimed at the discovery of a biomarker signature for TB diagnosis using a Nuclear Magnetic Resonance based metabolomics approach. In this study, we acquired 1H NMR spectra of blood serum samples of groups of healthy subjects, individuals with latent TB and of patients with pulmonary and extra-pulmonary TB. The resulting data were treated with uni- and multivariate statistical analysis. Results: Six metabolites (inosine, hypoxanthine, mannose, asparagine, aspartate and glutamate) were validated by an independent cohort, all of them related with metabolic processes described as associated with TB infection. Conclusion: The findings of the study are according with the WHO Target Product Profile recommendations for a triage test to rule-out active TB.